Effect of Al and W Contents on the Solidification and Solution Microstructure of Novel γ/γ′ Cobalt‐Base Superalloys. Issue 12 (17th October 2019) - Zhou, Xiaozhou; Fu, Huadong; Zhang, Yi; Xu, Huan; Xie, Jianxin
Abstract : The solidification and heat treatment characteristics of superalloys are key to engineering and practical applications. The solidification and solid solution behavior of γ / γ ′ cobalt‐base superalloys Co–30Ni– x Al–(15 −  x )W–5Cr–1Ta–4Ti ( x  = 7, 9, 11 abbreviated as 7Al8W, 9Al6W, and 11Al4W, respectively) are studied using directional solidification experiments. The results indicate that there are Laves phase, ( γ  +  γ ′)e eutectics, and ( β  +  γ ′)e eutectics in the interdendritic regions for the 7Al8W alloy. The solidification sequence of the 7Al8W alloy is L  →  L 1  +  γ  →  L 2  +  γ  + Laves →  L 3  +  γ  + Laves + ( β  +  γ ′)e  → L 4  +  γ  + Laves + ( β  +  γ ′)e  + ( γ  +  γ ′)e  →  γ  + Laves + ( β  +  γ ′)e  + ( γ  +  γ ′)e . As the Al content increases and the W content decreases, the Laves phase fraction in the alloy decreases and the ( β  +  γ ′)e eutectics fraction increases. The Laves phase completely disappears in the 11Al4W alloy. An unremovable μ phase forms in the 7Al8W alloy during solution treatment. The 9Al6W alloy and 11Al4W alloy can exhibit a γ single‐phase microstructure after single‐stage solution treatment (1250 °C for 1 h) and two‐stage solution treatment (1210 °C for 1 h + 1275 °C for 1 h), respectively. These experimental results are helpful for composition optimization, solidification, and solution treatment parameter determination of novel γ / γ ′ cobalt‐base superalloys. Abstract : This work reveals the effects of Al and W contents on the solidification and solution microstructure of γ / γ ′ Co‐base superalloys. As the Al content increases and the W content decreases, the Laves phase in the as‐cast microstructure reduces and eventually disappears, and the formation of μ phase during the solution treatment can also be suppressed.